TRPM8 knockdown relieved inflammatory response and cell apoptosis in pneumonia model induced by Streptococcus pneumoniae in vitro: TRPM8 knockdown relieved inflammatory response in pneumonia - Sheng, Kui; Sang, Linli; Ge, Hui (Cellular and Molecular Biology, 2023)
Streptococcus pneumoniae infection remains a leading cause of pneumonia-related deaths. Transient receptor potential melastatin 8 (TRPM8) exerts crucial roles in lung diseases. We first dissected the role of TRPM8 in pneumococcal pneumonia and the mechanism related to TRPM8 effects. TRPM8 expression and inflammation cytokines level were determined in 15 paired patients and controls. A549 cells were pretreated with si-TRPM8, followed by infection with S. pneumoniae D39 strain (D39). TRPM8 expressions in D39-treated cells were detected and the effect of TRPM8 inhibition on the viability, apoptosis, and inflammation induced by D39 was evaluated. To explore the mechanism underlying TRPM8 effects, cells in D39+si-TRPM8 group were further treated with MAPK activator (Anisomycin, ANIS). TRPM8 was highly expressed in patients and cell models at mRNA or/and protein levels. Cytokines of TNF-α, IL-1β and IL-6 were intensely upregulated in the serum samples of patients and cells infected with D39 (p<0.05). TRPM8 knockdown attenuated the reduced cell viability and increased cell apoptosis (reflected by the upregulation of Bax and downregulation of Bcl-2) in D39 group (p<0.05). The expression level of inflammation cytokines was lower in D39+si-TRPM8 group than D39 group (p<0.05). The protein levels of NF-κB p-p65 and p-p38 MAPK were intensely accumulated in D39 treated cells, while reduced by TRPM8 inhibition (p<0.05). ANIS addition significantly attenuated the altered cell viability, cell apoptosis and inflammation response in D39+si-TRPM8 group (p<0.05). TRPM8 knockdown relieved D39 infection-caused inflammation and cell apoptosis via NF-κB/MAPK signaling.